Pollution effect and effluent discharge on soil physico-chemical properties around cement factories - Yitagesu, Yohannes Habteyesus (Jour Med Resh and Health Sci, 2024)
The different research finding have stated that the cement factory dust particulate matter contributes a negative effect on soil health, a significant sources of heavy metal toxicity and crop yield reductions. In this study, two cement factories pollution effect and effluent discharge implication study were conducted on the effect of soil health and nutrient status of the study area. seventy soil samples at different distance from the factory (0-750m, 750-2000m & 2000m-3000m), and effluents sample from Mugher cement factory were collected and analyzed at Holeta Soil, plant and Water analysis Laboratory. Heavy Metals and major physico-chemical properties (TN, Oc, K, P, pH, Moisture, soil texture, Bulk density, SO4-S and Cation exchange capacity) were analyzed following the standard procedures. The content of heavy metals; Cu, Cr, Mn, Cd, Fe, Pb, As and Zn were executed using AAS. One-way ANOVA subjected to compare the mean values of each parameter with regardless to distance from the factories with SPSS statistical software. Soil pH is an excellent indicator of the suitability of a soil for plant growth and crop productivity. For most crops pH of 6 to 7.5 is optimal, this research findings result showed that the soil pH is neutral to moderately alkaline soil pH. The normal soil pH in the study areas are generally acidic, due to the continuous deposition of cement dust, soil pH was found slightly alkaline near the cement plants. The higher values electrical conductivity and bulk density were also noticed near to the cement plants. However, lower values of soil moisture content, soil organic carbon and total nitrogen content were found compared to far from the factory. Heavy metals level from factory effluent, Mugher location, of Cu, Mn and Cr are above the permissible limit set by FAO, not recommended for irrigation and cereal production activities. The effect of cement dust deposition on soil is more in areas nearer to the cement plants. This trend of soil physic-chemical properties change, may adversely affect the area and leads to multiple effects on flora, fauna and socio-economy of the area. The factory therefore should be monitor and control the emanates cement dust and effluent discharge before released to the environment.